Phenotypic and genotypic evaluation of Parkiplatycephala families: a proposal for pre-selection - Silva, Dandara Yasmim Bonfim de Oliveira [UNESP]; de Farias, Séfora Gil Gomes; Dias, Poliana Coqueiro; E Silva, Romario Bezerra; Dias, Bruna Anair Souto (FapUNIFESP (SciELO), 2023)
The objective of the study was to determine whether Parkia plat-ycephala families with superior morphophysiological traits perform consistently across four stages of early development (plantlets, seedlings, and juveniles at 34 and 60 months), as a means to assess the possibility of conducting pre-selection. For 21 morphophysiological traits, the following genetic parameters were estimated: heritability, coefficients of variation (genetic, relative, and environmental), accuracy, genetic and phenotypic correlation, percentage of coincidence (PC) of the best families, effective population size, and inbreeding in three progeny tests conducted under laboratory, nursery, and field conditions. Families of P. platycephala showed significant phenotypic and genotypic differ-ences. The traits evaluated show genetic control. The percentage of coincidence between the best families was more accurate when the selection intensity was greater than 50% (PC ≥ 52%). Based on the evaluated traits, a pre-selection strategy at the juvenile stage for P. platycephala was researched to effectively identify superior families.
Keywords: early selection; forest species; gecorrelation; Genetic improvement; genetic variability